High thermal conductivity aluminum nitride ceramic electrostatic chuck and method of making same

CN123022192APending Publication Date: 2026-10-30WUXI HYGOOD NEW TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610962186.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-30

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a high-thermal-conductivity aluminum nitride ceramic electrostatic chuck and a preparation method thereof, and belongs to the field of semiconductor manufacturing equipment. The electrostatic chuck comprises a dielectric layer, an electrode layer and a substrate layer. The dielectric layer is aluminum nitride ceramic, wherein the Y2O3 doping concentration continuously and monotonically decreases from the wafer adsorption surface side to the electrode side along the thickness direction, the concentration changes smoothly in any adjacent micro area, and there is no composition mutation macroscopic interface. The volume resistivity of the adsorption surface side is 10 8 ~10 11 Ω·cm, and the thermal conductivity of the electrode side is greater than or equal to 180 W / (m·K). During preparation, a green body with a composition step distribution is formed by using a multi-layer co-casting technology, the doped elements are smoothly transitioned through solid-phase diffusion after glue removal and integral sintering, and then the electrode and the substrate layer are integrated. The application can eliminate the interface thermal resistance and thermal stress mismatch problem, and has excellent thermal conductivity, adsorption performance and long-term reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor manufacturing equipment technology, specifically to a high thermal conductivity aluminum nitride ceramic electrostatic chuck and its preparation method. Background Technology

[0002] Electrostatic chucks (ESCs) are core components used in advanced semiconductor manufacturing processes to hold and temperature-control wafers. Aluminum nitride ceramics, due to their high thermal conductivity and coefficient of thermal expansion matching that of silicon, have become an ideal material for the dielectric layer of high-end ESCs.

[0003] To control resistivity, existing techniques typically involve uniformly doping aluminum nitride with sintering aids such as Y₂O₃. However, high doping levels introduce a large amount of grain boundary phases, severely reducing thermal conductivity. In recent years, some schemes have proposed using a multilayer abrupt structure, dividing the dielectric layer into independent sublayers with different compositions, each responsible for controlling resistivity and maintaining high thermal conductivity. However, this scheme results in clear physical interfaces between layers, leading to strong phonon scattering at the interfaces and generating additional interfacial thermal resistance. Furthermore, the differences in thermal expansion coefficients between layers cause interfacial stress concentration, making them prone to microcracks during thermal cycling.

[0004] Therefore, how to achieve synergistic optimization of resistivity and thermal conductivity in aluminum nitride electrostatic chucks, while eliminating the problems of interfacial thermal resistance and thermal stress mismatch in multilayer structures, is a technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0005] To address the aforementioned technical problems, this application provides a high thermal conductivity aluminum nitride ceramic electrostatic chuck and its preparation method. By constructing a gradient distribution of Y2O3 doping concentration that continuously varies from high to low along the thickness direction of the dielectric layer, the resistivity transitions smoothly along the thickness direction. This maintains the high resistivity of the surface layer to meet electrostatic adsorption performance while keeping the bottom layer in a low-doped or even undoped state to maximize thermal conductivity.

[0006] This invention discloses a high thermal conductivity aluminum nitride ceramic electrostatic chuck, comprising a dielectric layer, an electrode layer, and a substrate layer. The dielectric layer is aluminum nitride ceramic, wherein the Y₂O₃ doping concentration decreases continuously and monotonically along the thickness direction from the wafer adsorption surface to the electrode side, resulting in a smooth concentration change within any adjacent micro-intervals and the absence of macroscopic interfaces with abrupt compositional changes throughout the dielectric layer; the volume resistivity of the dielectric layer at the adsorption surface is 10⁻⁶. 8 ~10 11 The thermal conductivity of the dielectric layer electrode side is ≥180 W / (m·K), with a thermal conductivity of Ω·cm.

[0007] Furthermore, at any thickness location, the rate of change of Y2O3 concentration between adjacent micro-regions does not exceed 0.5 wt% / mm, thereby ensuring the uniformity of performance transition in each region of the dielectric layer. The Y2O3 doping concentration on the adsorption surface side of the dielectric layer is preferably 1.5 wt% to 3.0 wt%; the Y2O3 doping concentration on the electrode side is preferably 0.1 wt% to 0.5 wt%.

[0008] This invention also discloses a method for preparing the above-mentioned electrostatic chuck, comprising the following steps: Prepare aluminum nitride (AlN) slurries with a gradient series of Y2O3 doping concentrations; The multilayer co-casting technique is used to cast the green blank in order of decreasing doping concentration to form a green blank with a step-like compositional distribution. After debinding the green body, it is sintered in a nitrogen atmosphere to achieve a smooth transition of composition of Y2O3 between adjacent microlayers through solid-phase diffusion, forming a continuous gradient doped dielectric layer. Electrode paste is printed on the surface of the continuously gradient doped dielectric layer, and the electrodes and the substrate are integrated by co-sintering or diffusion bonding.

[0009] In the above preparation method, multilayer co-casting technology is key to achieving continuous gradient doping. By preparing a series of slurries with gradient Y₂O₃ doping concentrations and strictly controlling the doping concentration difference and single-layer thickness of adjacent cast layers, a microlayer stacked structure with an approximately step-like compositional distribution can be formed before sintering. During the subsequent integral sintering process, the Y₂O₃ between adjacent microlayers achieves a smooth transition of composition through high-temperature solid-state diffusion, ultimately forming a continuous gradient doped structure without macroscopic interfaces. Compared with existing technologies that require the separate preparation of multiple powders and the use of stepwise hydraulic molding, the method of this application has a shorter process flow, is simpler to operate, and is suitable for industrial mass production.

[0010] In the above preparation method, the difference in Y2O3 doping concentration between adjacent cast layers is ≤0.5 wt%, and in the multilayer co-casting technology, the thickness of the formed single-layer cast layer is ≤50 μm. The temperature of the debinding treatment is 400℃~600℃, and the time is 2~4 hours. The temperature of the integral sintering is 1800℃~1900℃, the holding time is 4~8 hours, and the applied axial pressure is 5MPa~30 MPa.

[0011] This application has the following beneficial effects: This application employs a gradient structure design with a continuously monotonically decreasing Y₂O₃ doping concentration along the thickness direction. This design enables the dielectric layer to achieve the desired resistivity on the adsorption surface side while maintaining high thermal conductivity on the electrode side, thus achieving synergistic optimization of resistivity and thermal conductivity. By replacing the multilayer abrupt structure with a continuous gradient structure, this application effectively avoids the thermal stress concentration problem caused by multilayer structures, significantly improving heat transfer efficiency and long-term reliability under thermal cycling. Furthermore, this application utilizes a multilayer co-casting combined with integrated sintering method. This requires only the preparation and sequential casting of a series of slurries, eliminating the need for complex step-by-step hydraulic and cold isostatic pressing processes. The process is short and easily scalable for industrial production. Detailed Implementation

[0012] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations.

[0013] Example 1

[0014] This embodiment provides a method for preparing a high thermal conductivity aluminum nitride ceramic electrostatic chuck, including the following steps: S1. Preparation of gradient series slurries: Using high-purity AlN powder as raw material, six slurries with Y2O3 doping amounts of 2.0 wt%, 1.6 wt%, 1.2 wt%, 0.8 wt%, 0.4 wt%, and 0.2 wt% were prepared respectively.

[0015] The specific preparation method is as follows: AlN powder, Y2O3 powder, dispersant phosphate ester, binder polyvinyl butyral, and plasticizer dibutyl phthalate are added to anhydrous ethanol as solvent, ball-milled and mixed for 6 hours, and after degassing, a uniform cast slurry is obtained.

[0016] The dispersant phosphate ester was added at 1.5 wt% of the weight of AlN powder, the binder polyvinyl butyral was added at 8 wt% of the weight of AlN powder, and the plasticizer dibutyl phthalate was added at 4 wt% of the weight of AlN powder.

[0017] S2. Multi-layer co-casting molding: The doctor blade casting method was used, with Y₂O₃ content decreasing sequentially: 2.0 wt%, 1.6 wt%, 1.2 wt%, 0.8 wt%, 0.4 wt%, and 0.2 wt%. Four layers of each slurry were cast, with a single layer thickness controlled at 25 μm, forming a total of 24 microlayers and a total thickness of 600 μm. After each slurry was cast, it was dried at 60℃ for 30 min before the next layer was cast to ensure initial bonding between layers.

[0018] S3. Overlapping and glue removal: The co-cast green preforms were warm-pressed together at 65℃ and 5 MPa pressure for 30 min. Then they were placed in a debinding oven and heated to 500℃ at a rate of 1℃ / min under a nitrogen atmosphere, and held at that temperature for 3 h to debind the adhesives and plasticizers.

[0019] S4. Integrated sintering: The debinding green body was transferred to a hot-pressing sintering furnace for densification sintering under a nitrogen atmosphere. The sintering regime was as follows: heating to 1850℃ at a rate of 5℃ / min, holding at that temperature for 6 hours, and applying an axial pressure of 10 MPa. During the sintering process, the Y₂O₃ between adjacent microlayers achieved a smooth transition of composition through solid-phase diffusion, ultimately forming a continuous gradient doped structure without macroscopic interfaces.

[0020] S5. Integrated Electrode and Substrate: Tungsten electrode paste was screen-printed onto the surface of the sintered gradient dielectric layer and dried at 130°C for 30 min. Then, co-sintering was performed under a nitrogen atmosphere at 1600°C for 2 hours to achieve a strong bond between the electrode layer and the dielectric layer. Finally, the dielectric layer was joined to the substrate layer using diffusion welding at 600°C, 30 MPa, and for 90 min, resulting in a complete aluminum nitride electrostatic chuck. The substrate layer was made of aluminum alloy 6061.

[0021] Example 2

[0022] This embodiment provides a method for preparing a high thermal conductivity aluminum nitride ceramic electrostatic chuck, including the following steps: S1. Preparation of gradient series slurries: Using high-purity AlN powder as raw material, six slurries with Y2O3 doping amounts of 1.5 wt%, 1.2 wt%, 0.9 wt%, 0.6 wt%, 0.3 wt%, and 0.1 wt% were prepared respectively.

[0023] The amount of dispersant phosphate ester added to the slurry is 1.5 wt% of the weight of AlN powder, the amount of binder polyvinyl butyral added is 8 wt% of the weight of AlN powder, and the amount of plasticizer dibutyl phthalate added is 4 wt% of the weight of AlN powder. The above raw materials are added to the solvent anhydrous ethanol, ball-milled and mixed for 6 hours, and after degassing, a homogeneous cast slurry is obtained.

[0024] S2. Multi-layer co-casting molding: The doctor blade casting method was used, with Y₂O₃ content sequentially decreasing: 1.5 wt%, 1.2 wt%, 0.9 wt%, 0.6 wt%, 0.3 wt%, and 0.1 wt%. Four layers of each slurry were cast, with a single layer thickness controlled at 25 μm, forming a total of 24 microlayers and a total thickness of 600 μm. After each slurry was cast, it was dried at 60℃ for 30 min before the next layer was cast.

[0025] S3. Overlapping and glue removal: The co-cast green preforms were warm-pressed together at 65℃ and 5 MPa pressure for 30 min. Then they were placed in a debinding oven and heated to 500℃ at a rate of 1℃ / min under a nitrogen atmosphere, and held at that temperature for 3 hours for debinding.

[0026] S4. Integrated sintering: After debinding, the green body is transferred to a hot pressing sintering furnace and heated to 1850°C at a heating rate of 5°C / min under a nitrogen atmosphere. It is held at this temperature for 6 hours and an axial pressure of 10 MPa is applied.

[0027] S5. Integrated Electrode and Substrate: The integration process is the same as in Example 1.

[0028] Example 3

[0029] This embodiment provides a method for preparing a high thermal conductivity aluminum nitride ceramic electrostatic chuck, including the following steps: S1. Preparation of gradient series slurries: Using high-purity AlN powder as raw material, six slurries with Y2O3 doping amounts of 3.0 wt%, 2.4 wt%, 1.8 wt%, 1.2 wt%, 0.6 wt%, and 0.3 wt% were prepared respectively.

[0030] The amount of dispersant phosphate ester added to the slurry is 1.5 wt% of the weight of AlN powder, the amount of binder polyvinyl butyral added is 8 wt% of the weight of AlN powder, and the amount of plasticizer dibutyl phthalate added is 4 wt% of the weight of AlN powder. The above raw materials are added to the solvent anhydrous ethanol, ball-milled and mixed for 6 hours, and after degassing, a homogeneous cast slurry is obtained.

[0031] S2. Multi-layer co-casting molding: The doctor blade casting method was used, with Y₂O₃ content sequentially decreasing: 3.0 wt%, 2.4 wt%, 1.8 wt%, 1.2 wt%, 0.6 wt%, and 0.3 wt%. Four layers of each slurry were cast, with a single layer thickness controlled at 25 μm, forming a total of 24 microlayers and a total thickness of 600 μm. After each slurry was cast, it was dried at 60℃ for 30 min before the next layer was cast.

[0032] S3. Overlapping and glue removal: The co-cast green preforms were warm-pressed together at 65℃ and 5 MPa pressure for 30 min. Then they were placed in a debinding oven and heated to 500℃ at a rate of 1℃ / min under a nitrogen atmosphere, and held at that temperature for 3 hours for debinding.

[0033] S4. Integrated sintering: After debinding, the green body is transferred to a hot pressing sintering furnace and heated to 1850°C at a heating rate of 5°C / min under a nitrogen atmosphere. It is held at this temperature for 6 hours and an axial pressure of 10 MPa is applied.

[0034] S5. Integrated Electrode and Substrate: The integration process is the same as in Example 1.

[0035] Example 4

[0036] This embodiment provides a method for preparing a high thermal conductivity aluminum nitride ceramic electrostatic chuck, including the following steps: S1. Preparation of gradient series slurries: Using high-purity AlN powder as raw material, six slurries with Y2O3 doping amounts of 2.0 wt%, 1.6 wt%, 1.2 wt%, 0.8 wt%, 0.4 wt%, and 0.2 wt% were prepared respectively.

[0037] The amount of dispersant phosphate ester added to the slurry is 1.5 wt% of the weight of AlN powder, the amount of binder polyvinyl butyral added is 8 wt% of the weight of AlN powder, and the amount of plasticizer dibutyl phthalate added is 4 wt% of the weight of AlN powder. The above raw materials are added to the solvent anhydrous ethanol, ball-milled and mixed for 6 hours, and after degassing, a homogeneous cast slurry is obtained.

[0038] S2. Multi-layer co-casting molding: The doctor blade casting method was used, with Y₂O₃ content sequentially decreasing: 2.0 wt%, 1.6 wt%, 1.2 wt%, 0.8 wt%, 0.4 wt%, and 0.2 wt%. Four layers of each slurry were cast, with a single layer thickness controlled at 40 μm, forming a total of 24 microlayers and a total thickness of 960 μm. After each slurry was cast, it was dried at 60°C for 30 min before the next layer was cast.

[0039] S3. Overlapping and glue removal: The co-cast green preforms were warm-pressed together at 65℃ and 5 MPa pressure for 30 min. Then they were placed in a debinding oven and heated to 500℃ at a rate of 1℃ / min under a nitrogen atmosphere, and held at that temperature for 3 hours for debinding.

[0040] S4. Integrated sintering: After debinding, the green body is transferred to a hot pressing sintering furnace, heated to 1900℃ at a heating rate of 5℃ / min under a nitrogen atmosphere, held for 8 hours, and subjected to an axial pressure of 30 MPa.

[0041] S5. Integrated Electrode and Substrate: The integration process is the same as in Example 1.

[0042] Example 5

[0043] This embodiment provides a method for preparing a high thermal conductivity aluminum nitride ceramic electrostatic chuck, including the following steps: S1. Preparation of gradient series slurries: Six slurries were prepared using high-purity AlN powder as raw material, with Y2O3 doping amounts of 2.0 wt%, 1.6 wt%, 1.2 wt%, 0.8 wt%, 0.4 wt%, and 0.2 wt%, respectively. The amount of phosphate dispersant added to the slurry was 1.5 wt% of the AlN powder weight, the amount of polyvinyl butyral binder added was 8 wt% of the AlN powder weight, and the amount of dibutyl phthalate plasticizer added was 4 wt% of the AlN powder weight. The above raw materials were added to anhydrous ethanol as solvent, ball-milled for 6 hours, and after degassing, a homogeneous casting slurry was obtained.

[0044] S2. Multi-layer co-casting molding: The doctor blade casting method was used, with Y₂O₃ content sequentially decreasing: 2.0 wt%, 1.6 wt%, 1.2 wt%, 0.8 wt%, 0.4 wt%, and 0.2 wt%. Four layers of each slurry were cast, with a single layer thickness controlled at 15 μm, forming a total of 24 microlayers and a total thickness of 360 μm. After each slurry was cast, it was dried at 60°C for 30 min before the next layer was cast.

[0045] S3. Overlapping and glue removal: The co-cast green preforms were warm-pressed together at 65℃ and 5 MPa pressure for 30 min. Then they were placed in a debinding oven and heated to 500℃ at a rate of 1℃ / min under a nitrogen atmosphere, and held at that temperature for 3 hours for debinding.

[0046] S4. Integrated sintering: After debinding, the green body is transferred to a hot pressing sintering furnace, heated to 1800℃ at a heating rate of 5℃ / min under a nitrogen atmosphere, held for 4 hours, and subjected to an axial pressure of 5 MPa.

[0047] S5. Integrated Electrode and Substrate: The integration process is the same as in Example 1.

[0048] Comparative Example 1 The difference from Example 1 is that the Y2O3 doping concentration in the dielectric layer is uniform at 1.5 wt%, with no gradient change, and the fabrication method includes the following steps: S1. Preparation of slurry: A single slurry with a Y2O3 doping content of 1.5 wt% was prepared using high-purity AlN powder as raw material.

[0049] The amount of dispersant phosphate ester added to the slurry is 1.5 wt% of the weight of AlN powder, the amount of binder polyvinyl butyral added is 8 wt% of the weight of AlN powder, and the amount of plasticizer dibutyl phthalate added is 4 wt% of the weight of AlN powder. The above raw materials are added to the solvent anhydrous ethanol, ball-milled and mixed for 6 hours, and degassed to obtain the cast slurry.

[0050] S2. Casting: The above slurry was cast into 24 thin layers with a single layer thickness of 25 μm using a doctor blade casting method, for a total thickness of 600 μm. Each layer was dried at 60°C for 30 min after casting.

[0051] S3. Overlapping and glue removal: The cast green bodies were warm-pressed together at 65℃ and 5 MPa pressure for 30 min. Then they were placed in a debinding furnace and heated to 500℃ at a rate of 1℃ / min under a nitrogen atmosphere, and held at that temperature for 3 hours for debinding.

[0052] S4. Integrated sintering: After debinding, the green body is transferred to a hot pressing sintering furnace, heated to 1850°C at a heating rate of 5°C / min under a nitrogen atmosphere, held at that temperature for 6 hours, and subjected to an axial pressure of 10 MPa.

[0053] S5. Integrated Electrode and Substrate: Tungsten electrode paste was screen-printed onto the surface of the sintered dielectric layer, dried at 130°C for 30 min, and then co-sintered at 1600°C for 2 hours under a nitrogen atmosphere. It was then bonded to the aluminum alloy substrate using a diffusion welding process at 600°C, 30 MPa, and held for 90 min.

[0054] Comparative Example 2 The difference from Example 1 is that the dielectric layer consists of three sublayers with independent composition, and the Y2O3 doping concentrations of each sublayer are 1.5 wt%, 0.8 wt%, and 0.1 wt%, respectively.

[0055] S1. Preparation of ceramic layer powder: Three powders with varying Y₂O₃ doping concentrations were prepared. Three AlN mixed powders with doping concentrations of 1.5 wt%, 0.8 wt%, and 0.1 wt% were prepared, respectively, according to the Y₂O₃ doping amount from high to low. Sintering aids and organic binders were also added to each powder. The powders were then ball-milled, dried, and sieved before use.

[0056] S2. Step-by-step hydroforming: S21. Use Y2O3 powder with a doping content of 0.1 wt% as the third ceramic layer powder, spread it evenly into the mold, and perform the first stage of hydraulic treatment. The pressing pressure is 10~20 MPa and the holding time is 2~5 minutes to form a dense third ceramic layer blank. S22. On the upper surface of the third ceramic layer blank, tungsten electrode paste is printed using screen printing to form a heating electrode layer, and then dried at 80~120℃; S23. Powder with a Y2O3 doping content of 0.8 wt% is evenly spread on the third ceramic layer and subjected to step-by-step hydraulic treatment to make it tightly bonded to the third ceramic layer to form the second ceramic layer blank. S24. On the upper surface of the second ceramic layer green body, tungsten electrode paste is printed using screen printing to form an electrostatic electrode layer, and then dried at 80~120℃. S25. Powder with a Y2O3 doping content of 1.5 wt% is uniformly spread on the second ceramic layer and subjected to step-by-step hydraulic treatment to make it tightly bonded to the second ceramic layer to form a first ceramic layer blank; the first ceramic layer, the second ceramic layer and the third ceramic layer together constitute a dielectric layer blank with a three-layer compositional step distribution.

[0057] S3. Cold isostatic pressing: The dielectric layer preform after the above-mentioned step-by-step hydraulic forming is taken out as a whole, covered with an elastic insulating layer, and placed in a cold isostatic press. It is held under pressure of 150~250 MPa for 10~30 minutes to further densify each layer of the preform.

[0058] S4. One-piece sintering: The dielectric preform after cold isostatic pressing is placed in a debinding furnace and heated to 500°C at a rate of 1°C / min under a nitrogen atmosphere. It is held at this temperature for 3 hours to debind the organic binder system. Then, the debinded preform is transferred to a hot pressing sintering furnace and heated to 1850°C at a rate of 5°C / min under a nitrogen atmosphere. It is held at this temperature for 6 hours and axial pressure of 10~30 MPa is applied for integral sintering.

[0059] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the thickness of the cast monolayer is 100 μm, and the preparation method includes the following steps: S1. Preparation of gradient series slurries: Using high-purity AlN powder as raw material, six slurries with Y2O3 doping amounts of 2.0 wt%, 1.6 wt%, 1.2 wt%, 0.8 wt%, 0.4 wt%, and 0.2 wt% were prepared respectively.

[0060] The specific preparation method is as follows: AlN powder, Y2O3 powder, dispersant phosphate ester, binder polyvinyl butyral, and plasticizer dibutyl phthalate are added to anhydrous ethanol as solvent, ball-milled and mixed for 6 hours, and after degassing, a uniform cast slurry is obtained.

[0061] The dispersant phosphate ester was added at 1.5 wt% of the weight of AlN powder, the binder polyvinyl butyral was added at 8 wt% of the weight of AlN powder, and the plasticizer dibutyl phthalate was added at 4 wt% of the weight of AlN powder.

[0062] S2. Multi-layer co-casting molding: The slurry is cast sequentially in descending order of Y2O3 content. Each type of slurry is cast in one layer, with a single layer thickness controlled at 100 μm, forming a total of 6 microlayers with a total thickness of 600 μm.

[0063] S3. Overlapping and glue removal: The co-cast green preforms were warm-pressed together at 65℃ and 5 MPa pressure for 30 min. Then they were placed in a debinding oven and heated to 500℃ at a rate of 1℃ / min under a nitrogen atmosphere, and held at that temperature for 3 hours for debinding.

[0064] S4. Integrated sintering: After debinding, the green body is transferred to a hot pressing sintering furnace and heated to 1850°C at a heating rate of 5°C / min under a nitrogen atmosphere. It is held at this temperature for 6 hours and an axial pressure of 10 MPa is applied.

[0065] S5. Integrated Electrode and Substrate: The integration process is the same as in Example 1.

[0066] The volume resistivity of the dielectric layer at different thicknesses was measured using a high-resistivity meter at a test voltage of 1000 V and a test temperature of 25℃. The thermal conductivity of the dielectric layer at different thicknesses was measured using a laser scintillation method at 25℃. The microstructure of the dielectric layer cross-section was observed using scanning electron microscopy (SEM) to determine the presence of macroscopic interfaces with abrupt compositional changes. A thermal cycling test (-40℃ to 150℃, 1000 cycles) was performed to check for microcracks in the dielectric layer and assess long-term reliability.

[0067] Table 1 Test results of the examples and comparative examples

[0068] Examples 1-5 all employed a gradient structure design where the Y₂O₃ doping concentration continuously and monotonically decreases from the wafer adsorption surface to the electrode side. Test results show that the volume resistivity on the adsorption surface side of Examples 1, 2, 4, and 5 is all within 10⁻⁶. 8 ~10 11 Within the target range of Ω·cm, the thermal conductivity on the electrode side reached or exceeded the threshold of 180 W / (m·K). In Example 3, due to the use of a higher upper limit for Y₂O₃ doping (3.0 wt%), the resistivity on the adsorption surface decreased to 5.1 × 10⁻⁶. 8 The resistivity is Ω·cm, close to the lower limit of the target range; meanwhile, the thermal conductivity on the electrode side is 176 W / (m·K), slightly below the threshold of 180 W / (m·K). This result indicates that when the Y₂O₃ doping concentration on the adsorption surface exceeds approximately 2.5 wt%, even with a low doping state maintained on the electrode side, the total volume fraction of the grain boundary phase in the entire dielectric layer still increases significantly, enhancing phonon scattering and leading to an observable decrease in thermal conductivity. Therefore, within the doping range of 2.0 wt% to 0.2 wt% used in Example 1, the overall balance between resistivity and thermal conductivity is relatively better.

[0069] SEM observations showed that none of the dielectric layers in Examples 1-5 exhibited macroscopic interfaces with abrupt compositional changes, and no microcracks were generated after 1000 thermal cycles, indicating that the continuous gradient structure effectively alleviated the problems of interfacial thermal resistance and thermal stress concentration. It is noteworthy that although Example 5 used the thinnest single-layer thickness, which is beneficial for the full diffusion of Y₂O₃, its sintering temperature and axial pressure were both at the lower limit of the process window, resulting in relatively insufficient driving force for green compact densification. The measured relative density of the sintered body was 97.8%, slightly lower than the 99.2% of Example 1. Residual pores caused additional scattering of phonon transmission, resulting in a lower thermal conductivity than Example 2. This indicates that in the design of continuous gradient structures, the single-layer thickness and sintering process parameters need to be optimized synergistically; simply reducing the layer thickness is not sufficient to continuously improve performance.

[0070] Comparative Example 1 employs a uniformly doped structure, with its adsorption surface resistivity within the target range, but its electrode-side thermal conductivity is only 138 W / (m·K), a decrease of approximately 28% compared to Example 1. Comparative Example 2 employs a three-layer structure with clear macroscopic interfaces between the layers. Although each sublayer performs resistivity regulation and thermal conductivity maintenance functions respectively, phonon scattering at the interface causes the overall thermal conductivity to drop to 151 W / (m·K). Furthermore, SEM observation after thermal cycling revealed microcracks extending along the interface within the dielectric layer of Comparative Example 2, with lengths of approximately 20–50 μm, indicating that the difference in interlayer thermal expansion coefficients indeed caused interlayer stress concentration. Although Comparative Example 3 uses a gradient series slurry, the single-layer thickness is too large, and the solid-phase diffusion distance of Y₂O₃ at 1850℃ / 6h is insufficient to completely eliminate the interlayer concentration difference. EPMA line scanning of the cross-section after sintering still shows traces of compositional steps. Its thermal conductivity is close to that of Comparative Example 2, but the failure mechanism is different. Comparative Example 2 is caused by phonon scattering at the abrupt interface, while Comparative Example 3 is caused by the residual pseudo-interface effect due to insufficient diffusion in thick layers.

[0071] A comparison of Examples 1-3 shows that, under the same casting and sintering process conditions, reducing the Y₂O₃ doping range is beneficial for improving the thermal conductivity on the electrode side, but the resistivity on the adsorption surface side increases accordingly to 7.2 × 10⁻⁶. 10 In practical applications, the resistivity (Ω·cm) may be unstable due to fluctuations in ambient humidity. Increasing the doping range can control the resistivity at a lower level, but it will compromise the thermal conductivity. Therefore, the doping range of 2.0 wt% to 0.2 wt% used in Example 1 achieves a relative balance between resistivity control margin and thermal conductivity maintenance.

[0072] Examples 4 and 5 investigated the effects of monolayer thickness and sintering process parameters. Example 4 used a 40 μm monolayer thickness. Under intensified sintering conditions of 1900℃ / 8h / 30 MPa, Y₂O₃ diffusion was sufficient, and the thermal conductivity still reached 184 W / (m·K), indicating that at higher temperatures and pressures, the monolayer thickness can be moderately increased to 40 μm without significantly affecting gradient smoothness. The results of Example 5 suggest that when the sintering temperature drops to 1800℃ and the pressure drops to 5 MPa, even with a layer thickness reduced to 15 μm, insufficient densification remains the main factor limiting thermal conductivity. Combining the results of Examples 4 and 5, the preferred monolayer thickness of 25 μm, sintering temperature of 1850℃, and axial pressure of 10 MPa in this application achieve a good balance between process controllability and performance indicators.

[0073] The adsorption performance of the electrostatic chuck samples from Examples 1-5 was evaluated using a vacuum adsorption force testing platform. The testing platform mainly consists of a vacuum chamber (ultimate vacuum ≤ 1 × 10⁻⁶). -3It consists of a DC high-voltage power supply (output voltage 0~3000 V, ripple coefficient <0.5%), a multi-channel pressure sensor array (range 0~50 kPa, accuracy ±0.1 kPa), a temperature-controlled heating stage (room temperature~300℃, temperature control accuracy ±1℃) and a wafer ejector pin desorption mechanism.

[0074] The test wafers were 8-inch (200 mm in diameter, 775 μm in thickness) single-crystal silicon wafers with a surface roughness Ra ≤ 0.5 nm. Before testing, the wafers were ultrasonically cleaned in a standard cleaning solution (SC-1: NH4OH / H2O2 / H2O = 1:1:5, 70℃) for 10 min, rinsed with deionized water, and dried with nitrogen gas to eliminate the influence of surface contamination on the adsorption capacity.

[0075] The specific testing steps are as follows: (1) Fix the electrostatic chuck sample to be tested on the temperature control heating stage to ensure good contact between the chuck surface and the heating stage, and place thermocouples on the back of the chuck to monitor the actual temperature.

[0076] (2) Place the cleaned silicon wafer at the center of the chuck's adsorption surface, close the vacuum chamber, and evacuate to <1×10⁻⁶. - 3 Pa, let stand for 30 min to eliminate the influence of surface adsorbed gas.

[0077] (3) Apply a DC 1000 V voltage to the electrode layer through a DC high voltage power supply and maintain it for 60 s to allow the adsorption force to reach a steady state.

[0078] (4) Use 36 pressure sensors (in a 6×6 array with a spacing of 30 mm) arranged below the adsorption surface to simultaneously read the adsorption force at each point and calculate the average adsorption force and coefficient of variation (CV%).

[0079] (5) The wafer is desorbed from the chuck surface by a uniform lifting rate of 0.5 mm / s through the ejector mechanism. The peak value of the pressure sensor reading at the moment of desorption is recorded as the desorption force, and the residual pressure sensor reading within 30 s after desorption is recorded as the residual adsorption force.

[0080] (6) Reduce the voltage to zero, apply a reverse voltage of -500 V and hold for 10 s to eliminate residual charge, then repeat steps (3)-(5) for the next test. Each sample was tested 5 times at three temperature points: 25℃, 100℃, and 200℃, and the average value was taken.

[0081] (7) While applying a working voltage of 1000 V, use a picoammeter (Keithley 6485) to monitor the leakage current between the electrode layer and the substrate layer and record the steady-state value.

[0082] Table 2. Electrostatic adsorption performance test results of Examples 1-5

[0083] The electrostatic adsorption performance test results of Examples 1-5 are shown in Table 2. The typical adsorption force requirement of the JR type electrostatic chuck in semiconductor processes is 15~25 kPa, and the adsorption force uniformity CV% is required to be <5%, the residual adsorption force is <2 kPa, and the leakage current is <5 nA.

[0084] In Example 1, the adsorption force at 25°C was 18.5 kPa, which was in the middle of the target range. As the temperature increased to 100°C and 200°C, the adsorption force decreased to 17.2 kPa and 15.8 kPa, respectively, a decrease of approximately 14.6%. The adsorption force uniformity CV of Example 1 was 3.2%, the residual adsorption force was 0.8 kPa, and the leakage current was 2.10 nA. All indicators met the practical application requirements of the electrostatic chuck.

[0085] Example 2, due to its lower Y₂O₃ doping range, resulted in a higher resistivity of the adsorption surface, leading to an adsorption force of only 12.3 kPa at 25°C, which is close to the lower limit of the JR-type electrostatic chuck's adsorption force. When the temperature rose to 200°C, the adsorption force further decreased to 8.7 kPa, failing to meet the requirements for reliable wafer fixation. This result indicates that while a lower doping range is beneficial for improving electrode-side thermal conductivity, excessively high resistivity of the adsorption surface leads to insufficient adsorption force, especially posing a risk of wafer slippage during high-temperature process steps. Therefore, the doping range of Example 2 should be used in conjunction with higher operating voltages or limited to low-temperature process scenarios in practical applications.

[0086] Example 3 employed a high Y₂O₃ doping range, resulting in a low resistivity of the adsorption surface and an adsorption force as high as 28.6 kPa at 25°C, exceeding the upper limit of the target range. While high adsorption force is beneficial for wafer fixation, the residual adsorption force reaches 4.5 kPa, requiring a large lifting force during desorption, posing a risk of scratching or cracking the back of the wafer. Furthermore, the leakage current of 6.80 nA exceeds the safety threshold of 5 nA, indicating that when the resistivity of the adsorption surface is too low, the dielectric layer's insulation margin is insufficient, potentially leading to dielectric breakdown due to localized electric field concentration during long-term operation. Therefore, although the doping range of Example 3 has some effect on the synergistic optimization of resistivity and thermal conductivity, it poses potential risks to the reliability of the electrostatic adsorption function.

[0087] The adsorption performance of Examples 4 and 5 is similar to that of Example 1. The adsorption uniformity CV of Example 4 is 3.5%, not significantly different from Example 1, indicating that under the enhanced sintering conditions of 1900℃ / 8h / 30 MPa, a 40 μm layer thickness can still form a sufficiently smooth gradient, and the uniformity of the electric field distribution is not significantly affected. The adsorption uniformity CV of Example 5 is 4.8%, close to the critical value of 5%, and the leakage current of 3.50 nA is higher than that of Example 1. This result is consistent with the phenomenon in Table 1 that the thermal conductivity of Example 5 is lower than that of Example 2, both pointing to the combined effect of insufficient densification under low-temperature and low-pressure sintering conditions.

[0088] Based on the test results in Tables 1 and 2, Example 1 is in the optimal balance range in terms of six indicators: thermal conductivity, resistivity, adsorption force, uniformity, residual adsorption force, and leakage current.

[0089] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A high thermal conductivity aluminum nitride ceramic electrostatic chuck, comprising a dielectric layer, an electrode layer, and a substrate layer, characterized in that: The dielectric layer is aluminum nitride ceramic, wherein the Y₂O₃ doping concentration decreases continuously and monotonically along the thickness direction from the wafer adsorption surface to the electrode side, resulting in a smooth concentration change between any adjacent micro-intervals and the absence of macroscopic interfaces with abrupt compositional changes throughout the dielectric layer; the volume resistivity of the dielectric layer at the adsorption surface is 10⁻⁶. 8 ~10 11 The thermal conductivity of the dielectric layer electrode side is ≥180 W / (m·K) Ω·cm.

2. The high thermal conductivity aluminum nitride ceramic electrostatic chuck according to claim 1, characterized in that: At any thickness location, the rate of change of Y2O3 concentration in adjacent micro-regions does not exceed 0.5 wt% / mm.

3. The electrostatic chuck according to claim 1, characterized in that: The Y2O3 doping concentration on the adsorption surface is 1.5wt%~3.0wt%.

4. The electrostatic chuck according to claim 1, characterized in that: The Y2O3 doping concentration on the electrode side is 0.1 wt% to 0.5 wt%.

5. A method for preparing an electrostatic chuck as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Prepare AlN slurries with a gradient of Y2O3 doping concentration; The multilayer co-casting technique is used to cast the green blank in order of decreasing doping concentration to form a green blank with a step-like compositional distribution. After debinding the green body, it is sintered in a nitrogen atmosphere to achieve a smooth transition of composition of Y2O3 between adjacent microlayers through solid-phase diffusion, forming a continuous gradient doped dielectric layer. Electrode paste is printed on the surface of the continuously gradient doped dielectric layer, and the electrodes and the substrate are integrated by co-sintering or diffusion bonding.

6. The preparation method according to claim 5, characterized in that: In the series of slurries, the difference in Y2O3 doping concentration between adjacent cast layers is ≤0.5 wt%.

7. The preparation method according to claim 5, characterized in that: In the aforementioned multilayer co-casting technology, the thickness of the single-layer cast layer is ≤50 μm.

8. The preparation method according to claim 5, characterized in that: The temperature for the glue removal process is 400℃~600℃, and the time is 2~4 hours.

9. The preparation method according to claim 5, characterized in that: The integral sintering temperature is 1800℃~1900℃, the holding time is 4~8 hours, and the applied axial pressure is 5 MPa~30 MPa.

10. The preparation method according to claim 5, characterized in that: The electrode paste is a tungsten paste or a molybdenum paste, the substrate layer is an aluminum alloy, and the diffusion welding is performed in a vacuum or inert gas atmosphere.